Development and in vitro characterization of new carnosine-loaded liposomal formulations - Russo, Stefano; Privitera, Anna; Greco, Giuliana; Di Pietro, Lucia; Cardaci, Vincenzo; Carota, Giuseppe; Sarpietro, Maria Grazia; Caruso, Giuseppe (Journal of liposome research, 2024)
Carnosine is an endogenous dipeptide characterized by a multimodal mechanism of action. However, its clinical potential is limited by serum and cytosolic carnosinases, which significantly reduce its bioavailability. Based on that, different research groups have worked on the development of new strategies able not only to prevent its rapid metabolization but also to improve its distribution and specific targeting. In the present study, the development and in vitro characterization of new liposomal formulations loaded with carnosine are described. Nanoliposomes, produced through Thin-Layer Hydration followed by Extrusion method, were first investigated for their physicochemical stability. Photon correlation spectroscopy and electrophoretic light scattering, assessing the stability of the formulations, showed a strong homogeneity-oriented tendency for up to two months. Particle size, polydispersity index, and zeta potential were determined through dynamic light scattering and electrophoretic light scattering, demonstrating an almost neutral charge of the formulation and an effective encapsulation of carnosine. The morphology assessment performed via scanning electron microscopy showed good conformity and polydispersity. Differential scanning calorimetry measurements suggest the ability of carnosine to stabilize the large unilamellar vesicles. Lastly, the newly developed carnosine-loaded liposomal formulations also showed a good safety profile in human microglia.
Gesehen am 02.04.2025